DEVELOPMENT PROPORTIONAL REASONING IN MATHEMATICS LEARNING ENVIRONMENT: SYSTEMATIC LITERATURE REVIEW - Ahmad Lutfi; Dadang Juandi; Bambang Avip Priatna Martadiputra (Universitas Cokroaminoto Palopo, 2023)
Proportional reasoning is closely related to everyday life. Conditions in schools show that there are still many students who still have difficulty in mastering proportional reasoning. Many studies have been conducted to overcome this. The purpose of this study is to provide an overview of research related to environmental mathematics learning interventions in developing students' proportional reasoning abilities. The method used is a systematic literature review (SLR) using the PRISMA protocol. The databases used are Google Scholar, Scopus, and ERIC in the 2018-2023 year of publication. There are several interventions carried out and discussed in the research results. Research related to interventions in the mathematics learning environment in developing students' proportional reasoning abilities has fluctuated in the 2018-2023 range, most were carried out in 2018 as many as 14 studies, most were carried out in junior high school demonstrations, namely 23 studies, the most widely used research method was quantitative method, namely 20 studies, Indonesia being the country that conducted the most research, namely 14 studies, and sample sizes in the range of 30-99 samples were the most widely used samples.